BORJUIS JAWA: TRANSFORMASI SOSIAL DI TENGAH KOLONIALISME ABAD XIX-XX - Irvan Tasnur; Naufal Raffi Arrazaq; Fitra Widya Wati (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
This study examines the emergence and development of the local bourgeoisie in Java in the 19th to 20th centuries. The main focus of the study is the transformation of the social class structure due to the implementation of liberal economic policies by the Dutch colonial government. The aim is to understand how the concept of "bourgeois" originating from the European socio-economic context was adapted in Javanese society. The method used is the historical method which includes heuristics (collecting sources), source criticism (data validation), data interpretation, and historiography (writing historical narratives), with the approach of Karl Marx's historical materialism theory. The results of the study show that the implementation of liberal economics in 1870 triggered the formation of a new social class that was different from the traditional aristocracy. The Javanese bourgeois class emerged from the lower priyayi class, such as village heads, high nobles, and traders who transformed into entrepreneurs. Although showing economic behavior similar to the European bourgeoisie, the Javanese bourgeoisie maintained its local identity. Until the early 20th century, they played an important role in the economy and national movements.